Repercusiones de la Co-Dependencia alcohólica en el sistema familiar de las mujeres asistentes al grupo de apoyo Al-Anón Esperanza de la Ciudad de Machala en el año 2013. - Aguirre Gallegos, Ronald Medardo (2013)
For the development of research we carry out a methodological process based on inductive, deductive, descriptive, qualitative, quantitative and hypothetical methods. As for the use of techniques we employ direct observation, interview, survey and signing.